THE INCLUSION OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS ON LESSONS OF PHYSICAL EDUCATION: PROFESSIONAL EXPERIENCE AND REFLECTION CRITICAL (Fiep Bulletin - online, 2014)
The inclusion of school pupils with special educational needs in mainstream education class joint is still a controversial issue that has caused a number of changes in the school network for the deployment of the so-called inclusive education. In the same way you can say that the discipline of supervised training curriculum in physical education is, in many cases, the first experience that the academic has before entering the labor market. It is through it that come the opportunity to work with students who have different educational needs and thus understand and experience the inclusion in the network of school education. The school and the faculty are together with their parents, those responsible for the education and training of children. Teachers of physical education use the movement as a way to teach, requiring seek strategies to include students with special educational needs in the form of participatory activities. In school environment, many facts are presented to the child, where she has the opportunity to live with the new and different that influences the acquisition of values and concepts that we all bear for life.
Keywords: Inclusive Physical Education; School; Vocational Training